The beginning of the end: a comparison of treatment completers and early dropouts in trainee-provided time-limited cognitive behavioral therapy. Issue 4 (2nd October 2022) - Urmanche, Adelya A.; Lipner, Lauren M.; Bloch-Elkouby, Sarah; Hunter, Elaine; Kaufmann, Jerzy; Warren, Jonathan T.; Weil, Gregory T.; Eubanks, Catherine F.; Muran, J. Christopher
ABSTRACT: About one in five clients drops out of treatment prematurely. Premature termination has been found to correlate with patient, therapist, and treatment factors, as well as complex interpersonal processes, including ruptures in the therapeutic alliance. This study examines the therapeutic alliance using a qualitative approach to patient-, therapist-, and observer-based data. The sample includes five trainee therapists, each of whom worked with one patient who terminated after the first or second session, and one who completed a cognitive-behavioral therapy protocol. The session(s) preceding premature termination in the drop case and the corresponding session(s) in the completer case were examined. Rupture resolution process was prevalent in both groups, though confrontation ruptures seemed more prevalent with completers and withdrawal ruptures were more clinically impactful with dropouts. Therapist awareness of process and responsiveness or contribution to rupture were identified as potential factors contributing to patient retention.